Development of Student Activity Sheets Based on The Realistic Mathematics Education (RME) Approach for Elementary School Students Pengembangan Lembar Kegiatan Siswa Berbasis Pendekatan Realistic Mathematics Education (RME) untuk Siswa Sekolah Dasar - Atika Nur Hidayati; Tri Maya Sari; Maratul Qiftiyah; Teguh Yunianto (Al-Mudarris: Journal Of Education, 2023)
This study aims to develop student worksheets with the RME approach in the mathematics subject matter of determining speed and discharge in grade V SD as well as knowing the validity of the product that has been developed. This research is a development research carried out using a procedural model, with development procedures according to the Ministry of National Education adapted from the Borg and Gall development procedures. The steps in the development procedure are: (1) analyzing the product being developed; (2) developing the initial product; (3) expert validation and revision; (4) small-scale field trials and product revisions; (5) large-scale field trials and final products. The instruments used included interview guide sheets, LKPD assessment sheets, test questions sheets, and student response scale sheets. Based on the assessment of the developed RME-based LKPD product, it is suitable for learning mathematics for class V SD/MI with speed and discharge material. This research product has been validated by material experts, media experts. The material expert validation score was 88.16, and the media expert validation score was 88. The developed RME-based LKPD product is effective in improving problem-solving skills. This is evidenced by the difference in n-gain acquisition between what students obtained through the pretest and posttest before and after the learning process using RME-based LKPD products. An increase in learning outcomes can be shown from the results normalized in the medium classification so that the level of effectiveness is effective. Therefore, mathematics LKPD with the RME approach on the subject matter of speed for class V SD is said to be of high quality and can facilitate problem solving skills based on valid, effective, and practical achievement criteria.